Solving linear multi-objective geometric programming problems via reference point approach - Bazikar, F.; Saraj, M. (Universiti Kebangsaan Malaysia, 2014)
In the last few years we have seen a very rapid development on solving generalized geometric programming (GGP) problems, but so far less works has been devoted to MOGP due to the inherent difficulty which may arise in solving such problems. Our aim in this paper was to consider the problem of multi-objective geometric programming (MOGP) and solve the problem via two-level relaxed linear programming problem Yuelin et al. (2005) and that is due to simplicity which occurs through linearization i.e. transforming a GP to LP. In this approach each of the objective functions in multi-objective geometric programming is individually linearized using two-level linear relaxed bound method, which provides a lower bound for the optimal values. Finally our MOGP is transformed to a multi-objective linear programming problem (MOLP) which is solved by reference point approach. In the end, a numerical example is given to investigate the feasibility and effectiveness of the proposed approach.